2019
DOI: 10.1371/journal.pone.0217556
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife usage indicates increased similarity between reclaimed upland habitat and mature boreal forest in the Athabasca Oil Sands Region of Alberta, Canada

Abstract: While there is no denying that oil sands development in the Athabasca Oil Sands Region (AOSR) has large impacts upon the habitat it disturbs, developers are legally required to return this land to “an equivalent land capability.” While still early in the process of reclamation, land undergoing reclamation offers an opportunity to study factors influencing reclamation success, as well as how reclaimed ecosystems function. As such, an Early Successional Wildlife Dynamics (ESWD) program was created to study how w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…The spontaneous appearance of wetlands on reclaimed areas presents an opportunity to consider the intentional facilitation of such features (e.g., via surface contouring or targeted plant seeding) as a potential complementary approach to compensating for habitat impacts to the pre-mine boreal landscape. Certainly, the presence of numerous small wetlands (at least 619 at Suncor Base Plant) has the potential to increase the ecological heterogeneity of upland reclaimed landforms, increase wildlife habitat suitability, and provide hydrologic functions (Little-Devito et al 2019;Hawkes and Gerwing 2019). For example, Hawkes and Gerwing (2019) found that wildlife (i.e., small mammal, large mammal, songbird, amphibian) communities on reclaimed uplands across the AOSR exhibited 31-62% (average 52%) similarity within 33 years of reclamation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spontaneous appearance of wetlands on reclaimed areas presents an opportunity to consider the intentional facilitation of such features (e.g., via surface contouring or targeted plant seeding) as a potential complementary approach to compensating for habitat impacts to the pre-mine boreal landscape. Certainly, the presence of numerous small wetlands (at least 619 at Suncor Base Plant) has the potential to increase the ecological heterogeneity of upland reclaimed landforms, increase wildlife habitat suitability, and provide hydrologic functions (Little-Devito et al 2019;Hawkes and Gerwing 2019). For example, Hawkes and Gerwing (2019) found that wildlife (i.e., small mammal, large mammal, songbird, amphibian) communities on reclaimed uplands across the AOSR exhibited 31-62% (average 52%) similarity within 33 years of reclamation.…”
Section: Discussionmentioning
confidence: 99%
“…Land reclamation occurs on active oil sands leases (both open pit mines and in-situ operations) concurrent with bitumen extraction activities. Most reclamation in the AOSR has targeted the re-establishment of upland forest habitat that is similar to the surrounding, naturally occurring boreal forest Hawkes and Gerwing 2019), although work aimed at directly reclaiming/restoring wetlands has also occurred. To date, wetland reclamation efforts have resulted in the establishment of numerous shallow open water and marsh wetlands on several surface mining leases including the first two mines established in the region: Syncrude's Mildred Lake lease and Suncor's Base Plant (Daly et al 2009;Daly et al 2010;Daly 2011;Pollard et al 2012;Daly et al 2012;Mollard et al 2015;Ketcheson et al 2016;Vitt et al 2016;Scarlett et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, for the breach and reference sites (B1 and Ref4) that exhibited significant changes in fish communities before and after breaching ( p = 0.01 and 0.002), the contribution of each fish species, including salmonids, to the observed change was explored using a similarities percentages (SIMPER) analysis (Clarke ; Clarke & Ainsworth ; Hawkes & Gerwing ). As part of this analysis we calculated the ratio of each variable's average dissimilarity to the standard deviation of dissimilarities (Diss/SD).…”
Section: Methodsmentioning
confidence: 99%
“…Oil Sands development is changing how wildlife uses the landscape, population densities, and species interactions both during the process of development and reclamation [4,55]. Changes in landscape features (i.e., connectivity) and usage by wildlife can change the predator-prey relationship changing the trophic position where wildlife are feeding [55].…”
Section: Plos Onementioning
confidence: 99%
“…The Canadian Oil sands, which is comprised of the Athabasca, Cold Lake, and Peace River deposits, covers approximately 142,200 km 2 and is situated in the middle of the Canadian boreal forest [ 3 ]. The Athabasca Oil Sands Region (AOSR) is the most heavily disturbed, where approximately 4,800 km 2 are undergoing surface mineable oil development, of which approximately 895 km 2 have been cleared or disturbed [ 3 , 4 ]. As a result, biota living in this region are exposed to many chemicals, including metals, primarily released during the upgrading of bitumen, and from fugitive dust related to mining activities [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%